HABILIDADE METACOGNITIVA E LEITURA EM LÍNGUA ESTRANGEIRA - Fantini, Márcia de Castro (Intercâmbio, 2010)
The purpose of this paper is to evaluate the metacognitive reading ability of proficient students of English as a Foreign Language. The research is grounded on the point of view that metacognitive ability is composed of two dimensions, knowledge of cognition and control of cognition (Flavell, 1978). We also consider the existence of a correlation between reading comprehension, strategy use and perception of strategy use. A Metacognitive Reading Questionnaire (Carrell, 1989) was selected as the most favorable instrument to deal with a population of 50 students.